The stability and antiapoptotic activity of Bm30K‐3 can be improved by lysine acetylation in the silkworm, Bombyx mori. Issue 4 (27th November 2019) - Ma, Yafei; Wu, Chengcheng; Liu, Jiahan; Liu, Yue; Lv, Jiao; Sun, Zihan; Wang, Dan; Jiang, Caiying; Sheng, Qing; You, Zhengying; Nie, Zuoming
Abstract: Acetylation is an important, highly conserved, and reversible post‐translational modification of proteins. Previously, we showed by nano‐HPLC/MS/MS that many nutrient storage proteins in the silkworm are acetylated. Among these proteins, most of the known 30K proteins were shown to be acetylated, including 23 acetylated 30K proteins containing 49 acetylated sites (Kac), indicating the importance of the acetylation of 30K proteins in silkworm. In this study, Bm30K‐3, a 30K protein containing three Kac sites, was further assessed in functional studies of its acetylation. Increasing the level of Bm30K‐3 acetylation by adding the deacetylase inhibitor trichostatin A (TSA) increased the levels of this protein and further inhibited cellular apoptosis induced by H2 O2 . In contrast, decreasing the level of acetylation by adding the acetylase inhibitor C646 could reduce the level of Bm30K‐3 and increase H2 O2 ‐induced apoptosis. Subsequently, BmN cells were treated with CHX and MG132, and increasing the acetylation level using TSA was shown to inhibit protein degradation and improve the stability of Bm30K‐3. Furthermore, the acetylation of Bm30K‐3 could compete with its ability to be ubiquitinated, suggesting that acetylation could inhibit the ubiquitin‐mediated proteasome degradation pathway, improving the stability and accumulation of proteins in cells. These results further indicate that acetylation might regulate nutrition storage and utilization in Bombyx mori, which requires further study. Abstract : Many 30K proteins are acetylated in silkworm and Bm30K‐3, a 30K protein, has been shown to be regulated by acetylation by altering their protein stability and antiapoptotic activity. Research Highlights: Lots of 30K proteins are acetylated in silkworm. Acetylation can enhance the stability and antiapoptotic activity of Bm30K‐3 by competing with its ubiquitination. Acetylation might regulate nutrient storage and utilization in Bombyx mori .